PERILAKU PENYIMPANGAN PENGISAP LEM DI KALANGAN REMAJA (STUDI TERHADAP 5 REMAJA PENGISAP LEM DI KELURAHAN KANDIS KOTA) - Juan Andoli Panggabean; Neri Widya Ramailis (UIR PRESS, 2025)
This study aims to analyze the factors influencing glue-sniffing behavior among adolescents in Kandis Kota Village. The indicators examined include educational background, economic conditions, daily activities, and other factors that are presumed to contribute to the emergence of such behavior. This research employs a qualitative descriptive method with a case study approach involving twelve informants, consisting of five adolescent glue sniffers, five parents, one local resident, and one village official. The research was conducted in Kandis Kota Village, Siak Regency. Data collection techniques included observation, interviews, and documentation. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. In addition, this study applies Differential Association Theory to strengthen the analysis. The results indicate that, based on the perspective of Differential Association, glue-sniffing behavior emerges due to peer influence and incorrect social learning processes. Based on the findings, it is recommended that various parties including families, neighbors, the surrounding community, schools, and the village government—be involved in efforts to guide and rehabilitate adolescents who have fallen into gluesniffing behavior.